Effect of tartaric acid as a structure-directing agent on different ZnO morphologies and their physical and photocatalytic properties - Sumetha Suwanboon (2018)
© 2018 Elsevier Ltd and Techna Group S.r.l. Among the semiconductor metal oxide photocatalysts, ZnO is one of the most popular due to the fact that its surface can be easily modified by a structure-directing agent, in order to improve its properties for photocatalytic processes. In this study, ZnO particles with different morphologies were successfully synthesized via a precipitation method. The mole ratio of tartaric acid to zinc nitrate significantly affected the particle shape. This morphological change in the ZnO particles drove the photocatalytic degradation of an aqueous methylene blue (MB) solution. The best photocatalytic degradation was obtained from ZnO particles with rod-like structures. Photocatalytic degradation of about 100% under UV radiation and 98% under visible light was obtained after 180 min when synthesized ZnO particles when R = 5 were used as a photocatalyst.